C2H2O4 + 2NaOH -->> C2O4Na2 +2H2O
Oxalic acid + Sodium hydroxide -->> sodium oxalate+ water
B.Cu + 2NO3- + 4H+ → Cu2+ + 2NO2 + 2H2O
a balanced equation for the reaction of hydrochloric acid and ammonia solution is given below.HCL(aq) + NH3(l) ---> NH4+(aq) + Cl-(aq) complete .This is the balanced chemical equation .
Na2SO4 +CaCl2---------------> 2NaCL +CaSo4
Simplified. 2NaOH + H2SO4 -> Na2SO4 + 2H2O
Ca(NO3)2 + Na2CO3 >> CaCO3 + 2NaNO3
One balanced equation for this reaction in aqueous solution is: Cu+2 + 2 AgNO3 -> 2 Ag + Cu(NO3)2.
zinc + ethanol + water + chloroform + copper sulphate solution
3Ca(NO3)2 + 2Na3PO3 >> Ca3(PO3)2 + 6NaNO3
The complete balanced equation is Pb(NO3)2 (aq) + K2SO4 (aq) -> 2 KNO3 (aq) + PbSO4 (s). The total ionic equation is Pb+2 (aq) + SO4-2 -> PbSO4 (s).
This equation is: 2CH3COOH + Na2CO3 --> 2NaCH3COO + CO2 + H2O .
Pbs + 2Ag(NO3) -> 2Ags + Pb(NO3)2
2KBr + 2H2O----->2KOH + Br2 + H2(g) this is the reaction in electrolysis of KBr in aqueous solution
write chemical equation for the reaction between viscose solution and sulphuric acid
NaCl(aq) + AgNO3(aq) --> NaNO3(aq) + AgCl(s) This is an example of a double replacement/displacement reaction.
If the HCl is in solution in water and the iron is solid, the most likely reaction is Fe + 2 HCl = FeCl2 + H2.
2MnO4- + 6H+ + 5(COOH)2 ----> 10CO2 + 2Mn2+ + 8H2O
2(FeBr3) + 3(Cl2) --> 2(FeCl3) + 3(Br2)
Cu2+ + 4NH3 ----> [Cu(NH3)4]2-
The BaSO4 (barium sulfate) will precipitate out of solution because it is insoluble, whereas the KCl2 is soluble and will remain dissolved. The balanced equation is: K2SO4 + BaCl2 -----> 2KCl + BaSO4
limewater is a solution of calcium hyroxide and calcium hydroxide is a base.
The chemical reaction isȘCaCl2 + Na2CO3 = CaCO3 + 2 NaCl
Mg (s) + 2 HNO3 (aq) --> H2 (g) + Mg(NO3)2 (aq)
There is no equation as there is no reaction between urea and water, urea just dissolves in water forming a solution.
If the specified reagents are in aqueous solution when reacted, the actual reaction occurs according to the balanced equation 2 Al+3 (aq) + 3 S-2 (aq) -> Al2S3 (s). If a full compound equation is preferred, that would be 2 Al(NO3)3 + 3Na2S -> 6 NaNO3 + Al2S3.